Dolomite Beach as a Tourist Attraction in Manila as Perceived by Local Residents: Basis for Tourism Promotion - Andrea Michlei P. Perez; Raina Jonice B. Reynoso; Sean Pierce T. Salangsang; Bianca Karyl B. Tañaquin; Pia Angela P. Valenzona; Rovena I. Dellova (Research Synergy Foundation, 2024)
Dolomite Beach, also known as Manila’s first man-made beach, is a fake sand beach formed through the process of nourishment on Manila Bay in Manila, Philippines. This is a new addition to Manila’s tourism industry. This study aims to make Dolomite Beach an effective tourist hotspot for Manila by increasing its significance and positioning it as a top attraction. It adopts a quantitative approach using Frequency Distributions, Weighted Means, and Standard Deviations through a descriptive study with 383 participants. Moreover, local residents had a high perception of Dolomite Beach as a tourist destination. The survey results show that, despite some initial controversy surrounding its construction, the majority of respondents favored of turning Dolomite Beach into a tourist attraction. The respondents felt excited when it was featured among the things to do in Manila for tourists. Many respondents expressed support for the establishment of an artificial white sandy beach in the city and looked forward to increased local and international tourism while providing more job opportunities for people who live in Manila. The benefits are many, not only for the residents of Manila but also for the overall community. The proactive involvement of residents, who are important players in the tourism industry, drives tourism growth. Therefore, this study shows that Dolomite Beach can be one of Manila’s leading tourist attractions.